ChemInform Abstract: Palladium‐Catalyzed Route to Three‐Component, One‐Pot Sequential Synthesis of Functionalized Cyclazines: 2, 2a1, 4‐Triazacyclopenta[cd]indenes. Issue 52 (24th December 2013) - Yang, Anjiang; Jiang, Ruwei; Khorev, Oleg; Yu, Ting; Zhang, Yongliang; Ma, Lanping; Chen, Guohua; Shen, Jingkang; Meng, Tao
Abstract The synthesis of cyclazines involves initial three‐component condensation and a Pd‐catalyzed intramolecular α‐arylation of an α‐aminocarbonyl functionality.